Increased ocean heat transports and warmer climate - Rind, D.; Chandler, M. (1991)
The impact of an increased ocean heat transport on climate is investigated in the framework of the GISS GMC model described by Hansen et al. (1983), using two scenarios: one starting from warmer polar temperatures/no sea ice and the other from the current ocean conditions. A 20-percent increase in cross-equatorial heat transport was sufficient to melt all sea ice; it resulted in a climate that was 2 C warmer for the global average, with values some 20-deg warmer at high altitudes and 1-deg warmer near the equator. It is suggested that the hydrological and dynamical changes associated with this different climate regime may be self-sustaining and, as such, would account for the high-latitude warmth of climates in the Mesozoic and Tertiary periods and the decadenal-scale climate fluctuations during the Holocene.